Legal Environmental Constraints: General Theoretical Aspect - Galina Moroz (Vasyl Stefanyk Precarpathian National University, 2018)
The article studies the conceptual basis and the general essential characteristics of public environmental requirements and constraints, focusing on the notion of legal environmental constraints as specific sectoral imperative means of regulating environmental safety enforcement, on their meaning, system, and representation in the national legislation. It is concluded that legal environmental constraints are stated and specified in regulatory acts of different legal force, different sectoral affiliation, and that the specific legislation on public environmental constraints is quite multifaceted. The article proves the necessity to systematize and unify the existing environmental requirements and proscriptions as well as to generalize the experience of their practical application in order to achieve ecologically significant aims. The research supports the proposal regarding the necessity to carry out the reform of the codification of the environmental law in the sphere of environmental safety enforcement as well as to legislate on environmental requirements and constraints by including them in a systematic way in the future code of environmental law, i.e. the Environmental Code of Ukraine.